2014
DOI: 10.1002/pola.27174
|View full text |Cite
|
Sign up to set email alerts
|

Chain‐growth condensation polymerization approach to synthesis of well‐defined polybenzoxazole: Importance of higher reactivity of 3‐amino‐4‐hydroxybenzoic acid ester compared to 4‐amino‐3‐hydroxybenzoic acid ester

Abstract: Application of chain‐growth condensation polymerization (CGCP) to obtain well‐defined polybenzoxazole (PBO) was examined. CGCP of both phenyl 3‐{(2‐methoxyethoxy)methoxy (MEM‐oxy)}‐4‐(octylamino)benzoate (1b) (para‐substituted monomer) and phenyl 4‐MEM‐oxy‐3‐(octylamino)benzoate (3b) (meta‐substituted monomer) was examined in the presence of metal disilazide base and phenyl 4‐nitro‐ or methylbenzoate 2 as an initiator. Polymerization of the latter monomer, but not the former, afforded polymer with controlled m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Monomer 5 with a methoxyethoxymethyl (MEM)-protected hydroxyl group and OOB-protected amino group afforded the corresponding polyamide, although the para counterpart was hardly polymerized. The protecting groups on the oxygen and amide nitrogen of the polyamide were simultaneously removed with TFA to afford well-defined poly­(amidophenol), which was converted to poly­(benzoxazole) by heating . AB 2 -type monomer 6 also underwent CGCP to give a hyperbranched polyamide, the molecular weight of which can be controlled up to 40000 while retaining low polydispersity ( M w / M n < 1.2). …”
Section: Cgcp Based On the Substituent Effectmentioning
confidence: 69%
See 2 more Smart Citations
“…Monomer 5 with a methoxyethoxymethyl (MEM)-protected hydroxyl group and OOB-protected amino group afforded the corresponding polyamide, although the para counterpart was hardly polymerized. The protecting groups on the oxygen and amide nitrogen of the polyamide were simultaneously removed with TFA to afford well-defined poly­(amidophenol), which was converted to poly­(benzoxazole) by heating . AB 2 -type monomer 6 also underwent CGCP to give a hyperbranched polyamide, the molecular weight of which can be controlled up to 40000 while retaining low polydispersity ( M w / M n < 1.2). …”
Section: Cgcp Based On the Substituent Effectmentioning
confidence: 69%
“…meta -Substituted phenylene monomers undergo CGCP, leading to polyamides under optimized conditions, although the inductive effect is less efficiently transmitted, compared to the resonance effect (Table ). Monomer 5 with a methoxyethoxymethyl (MEM)-protected hydroxyl group and OOB-protected amino group afforded the corresponding polyamide, although the para counterpart was hardly polymerized.…”
Section: Cgcp Based On the Substituent Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenyl ester monomer (1g) has been previously utilized to prepare a variety of aromatic polyamide structures by CGC polymerization and is typically the ester of choice with these polymerizations, due to its relatively high reactivity, compared with the methyl ester. [ 29,36–39 ] In addition, the preliminary solubility studies discussed above demonstrated that the resulting solutions for all the tested phenoxides, derived from the phenyl ester monomers (1g‐1k), were soluble. Based on these factors, the effectiveness of the different phenyl ester monomers in CGC polymerizations was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Looking now at the synthesis of fully aromatic polyamides, it is well-known that step-growth condensation polymerization is the main route. Chain-growth condensation polymerization (CGCP) was also proposed to give controlled and living characteristics to their synthesis. This approach was also proposed for the synthesis of aromatic poly­(ether ketone) for instance …”
Section: Introductionmentioning
confidence: 99%